One flew over the cuckoo’s clock: selling exclusivity through conspicuous goods on evolution - Oosterman, Naomi (Crime and art, 2021)
Despite the increase of specialised law enforcement and commercial art crime databases concerning the registration of luxury products, it remains an often-overlooked category in art crime research. This chapter analyses the market for luxury products, focusing specifically on watches, jewellery, and designer clothing, on defunct anonymous marketplace Evolution, which was active between January 2014 and March 2015. We argue that this marketplace works as a way to buy exclusivity through the purchase of both original and counterfeited luxury goods, here called ‘conspicuous goods’. The goods we focus on in our analysis endow cultural value, and their possession allows consumers to display a higher level of distinction. However, rather than looking at consumers who desire to differentiate themselves by purchasing these objects, we were more interested in how the market is structured to best sell these products. Therefore, we have implemented a series of statistical analyses on the market supply, focusing on the type of traded object, their brand, and the average prices in Bitcoin, finding that a brand effect on price is at work both in counterfeited and original conspicuous goods. This signals that the market is aware of the dynamics of conspicuous goods and its sellers behave accordingly.